ANALISIS KESULITAN BELAJAR SISWA KELAS XI TEKNIK BISNIS SEPEDA MOTOR DI SMK NEGRI 4 KOTA SERANG PADA MATA PELAJARAN PEMELIHARAAN MESIN SEPEDA MOTOR - Syamsul Munawar; Ahmad Habibi; Hamid Abdillah (LPPM Universitas Cipta Mandiri, 2025)
Learning disability is a difficulty where students experience obstacles in learning that can cause students to experience low achievement or learning outcomes. In the class XI motorcycle engine maintenance subject of Motorcycle Business Engineering at SMKN 4 Serang City, where in the midterm assessment that has been carried out 77.4% of students' scores have not reached KKM. For this reason, this study aims to analyze the learning difficulties of class XI motorcycle business engineering students at SMKN 4 Serang City on motorcycle engine maintenance subjects. Self-learning difficulties can be caused by several factors. This research method is Quantitative descriptive. The data obtained in this study was through a questionnaire questionnaire given to 40% of students from all class XI motorcycle business engineering students at SMKN 4 Serang City. This questionnaire was given using google from to identify learning difficulties they experienced. The results showed that class XI students of Motorcycle Business Engineering experienced difficulties in learning. These difficulties are caused by factors of learning materials that are difficult to understand (41.7%), ineffective teaching methods (0%), lack of adequate learning resources (33.3%), lack of direct practice (16.7%), a sense of disinterest in learning materials (8.3%).